Interprofessional Education: A Pilot for Future Collaboration. - HOCHSTEIN, LISA (Clinical Laboratory Science)
Interprofessional education (IPE) has become an integral pedagogy within the St. John's University College of Pharmacy and Health Sciences Department of Clinical Health Professions. An interprofessional case study activity was developed and incorporated into the Clinical Laboratory Sciences (CLS) and Physician Assistant (PA) programs. A pneumonia case involving aspects of patient care relevant to both programs was created. To not interfere with courses currently in progress for both programs, the event occurred during lunch hour and both programs asked for student volunteers. Ten students in total participated. Students worked together to better understand each other's role in diagnosing the patient, emphasizing team practice. PA students illustrated techniques in history and physical examination. CLS students then led the PA students into a mock laboratory and shared examples of pneumococcal plating and microscopic isolation for diagnosis confirmation. At the conclusion of the event, students evaluated their experience. Using role perception questionnaires, CLS and PA students indicated greater perceived value for one another's profession at activity completion. Evaluations indicated that students felt this was a worthwhile experience and that they learned a lot about each other's role in patient care. They also indicated that they would like to have similar programs in the future.